(untitled) (Anclajes, 2024)
The posthumous publication of Paris-Austerlitz (2016) by the Spanish writer Rafael Chirbes (1949-2015) was celebrated in certain media as a coming out of the closet, thus following a founding script of gay pride. In addition, the recent publication of Chirbes’ Diaries in two volumes (2021, 2022) demonstrates the relevance of male homosexual pain as the genesis of the creative process in the posthumous novel. The tension between homosexual pride and pain in the reception of these texts contributes not only to the public notoriety of Rafael Chirbes as a writer, but also provides a crucial knowledge about a productive relationship between sexuality and literary genres. Chirbes’ autobiographical writing demonstrates the political contingency of an affective experience that reproduces and transforms the expectations of gender and sexuality, while forcing us to reconsider the triumphalist rhetoric of gay pride.